Pengaruh Total Asset Turnover, Debt to Equity Ratio, Return on Asset, Firm Size dan Cash Ratio terhadap Dividend Payout Ratio pada Perusahaan yang Tergabung dalam Indeks Kompas-100 di Bursa Efek Indonesia Periode 2013-2018 - Wandi Jackson; Mia Laksmiwati (Penerbit Goodwood, 2021)
Purpose: This study aimed to determine the effect of total asset turnover, debt to equity ratio, return on assets, firm size and cash ratio on dividend payout ratio in companies included in the Kompas-100 Index on the Indonesia Stock Exchange 2013-2018. Research Methodology: Purposive sampling was used to collect data. Based on the criteria established and obtained, samples from ten public companies in the index Kompas-100 representing the total number of up to 100 companies were obtained. The testing of hypotheses was used as the instrument for analysis, processed through SPSS version 20 and Microsoft Excel 2010. Results: This study indicates that FS has a negative and significant influence on the DER, while the TATO, DER, ROA, and CR do not influence the DPR.